PERALIHAN SAHAM PT.TERTUTUP KEPADA KOPERASI DITINJAU DARI UNDANG-UNDANG NO.40 TAHUN 2007 DAN UNDANG-UNDANG NO.17 TAHUN 2012 - Mahmul Siregar; Windha Windha (TRANSPARENCY, 2014)
Limited liability company is a legal entity which capital is wholly divided into shares, the shares can be transferred to various kinds of interest in order to achieve the company's goals. Transfer of shares can be done, among others, to the cooperative which is a legal entity and can be established by a natural person or legal entity. The formulation of the issues discussed in this paper is how the capital in the limited liability company and capital in the cooperative, how are requirements and procedures for transfers of shares in a limited liability company, how to transfers of shares from enclosed limited liability company to cooperatives in terms of Law No. 40 of 2007 on Limited Liability Company and Law No.17 of 2012 on Cooperatives. Research methods used in the writing of this thesis is that the normative legal research methods or ways of researching the existing library materials. The first phase of the normative legal research is research aimed at obtaining objective law (legal norms), which is conducting research on legal issues. The second phase of the normative legal research is research aimed at obtaining subjective laws (rights and obligations). Research used are descriptive and used qualitative approaches that aim to understand and grasp the symptoms are examined. Data collection tools include the study of librarianship, legislation, books, scientific papers, etc. The result of this research the limited liability company's capital comes from shareholders who incorporate capital into the company, while the cooperative capital is derived from primary deposits and certificates of cooperative capital besides capital sources can be obtained from grants, loans from other parties such as banks, non-banks, cooperatives, or from members of cooperatives or other cooperative or can also be obtained from capital investments; second, the terms and procedures for transfer of shares has been stipulated in Law No. 40 of 2007 on Limited Liability Company, among others, through the offering will be sold in advance if, needed the approval organ of the company, or with the permission of the relevant agencies such as the Coordinating Agency for Investment (BKPM). Transfers of shares can be done with sale and purchase agreements and grants; third, transfers of shares of enclosed limited liability company to the cooperative if in the terms of Law No. 40 of 2007 on Limited Liability Company and Law No.17 of 2012 on Cooperatives is that the transition of ownership of shares means the transition to all things that have anything to do with the rights and obligations attached to the stocks concerned and carried out, among others, such as sale and purchase agreements and grants. The reasons for the transition of the enclosed limited liability company's shares to the cooperative if the company is selling stock, then there is an indication that the company is in need of additional capital, but when the company donated the shares to the cooperative, then this is a form of additional capital given by the company to the cooperative to promote itself. With the transfer of these shares, the right of shares’ ownership has changed.